Synthesis and anticonvulsive activity of new 1,3-diazaadamantane derivatives - Harutyunyan, A. D.; Gevorkyan, K. A.; Galstyan, M. V.; Paronikyan, R. G.; Nazaryan, I. E. («Գիտություն» հրատ.)
The work is devoted to the synthesis and study of the neurotropic activity of some derivatives of 3,7-diazabicyclo/3.3.1/nonanes. For this, various 5,7-dialkyl, methylphenyl, diphenyl 1,3-diazaa-damantanes 1 were synthesized, which, upon interaction with acid chlorides of aliphatic, aromatic and heterocyclic acids, were converted into the corresponding 3,7-diazabicyclo/3.3.1/nonanes. The anticonvulsant activity of the synthesized compounds was studied. Among them, substances with pronounced anticorazole activity were identified. Работа посвещена синтезу и изучению нейротропной активности некоторых производных 3,7-диазабицикло/3.3.1/нонанов. Для этого были синтезированы различные 5,7-диалкил, метилфенил-, дифенил-1,3-диазаадамантаны 1, которые при взаимодействии с Cl-ангидридами алифатических, ароматических, карбоциклических и гетероциклических кислот превращены в соответсвующие 3,7-диазабицикло/3,3,1/нонаны. Изучена противосудорожная активность синтезированных соединений, среди них выявлены вещества с выраженной антикоразоловой активностью. Սինթեզվել են 5,7-դիրքերում տարբեր ալկիլ, ալկիլֆենիլ, դիֆենիլ խմբեր պարունակող 1,3-դիազաադամանտաններ: Վերջիններիս փոխազդեցությունը տարբեր ալիֆատիկ, արոմատիկ, կարբոցիկլիկ, հետերոցիկլիկ թթուների քլորանհիդրիդների հետ հանգեցրել է համապատասխան 3,7-դիազաբիցիկլոնոնանների ստացման: Ուսումնասիրվել են սինթեզված միացությունների հակակորազոլային հատկությունները, որոշ միացություններ ցուցաբերել են արտահայտված կորազոլային ակտիվություն:
Keywords: Chemistry